Boats don't fish, people do: A sociological contribution towards holistic fisheries bycatch management - Fanny Barz (Johann Heinrich von Thünen-Institut, 2022)
People have always been utilizing natural resources from the sea with various impacts on fish stocks and the marine environment. An issue that arises from humans', specifically fishers' interaction with the sea, is the entanglement of marine birds and mammals in fishing gears, in particular gillnets, as a result of which these air-breathing animals drown. These incidents are called bycatch. Gillnets have a long history and tradition in fishing in the Baltic Sea and are also one of the most common gears worldwide. Bycatch of seabirds and marine mammals in gillnet fisheries is therefore a hazard for conservation globally. Measures on bycatch mitigation in fisheries management so far are mostly based on technological and ecological findings. There is often a lack of knowledge concerning the heterogeneity of fishers' actions and drivers, despite its importance for effective fisheries management. This dissertation considered the case of the German gillnet fleet in the Baltic Sea to generate an ontological understanding of fishers' social practices to inform management and develop bycatch mitigation measures. Natural resource sociology offers the lens to look at this objective. In this dissertation the praxeological theory of structuration, extended by the concept of agency by is applied to the research question. The qualitative empirical research was conducted applying problem-centred interviews, analysed with documentary method. An expert-workshop about political and administrative aspects of bycatch management complemented the empirical research. With the praxeological view and in applying the concept of agency, three types of fishers' dominating agency were distinguished: (i) Fishers with a dominating projective (future-oriented) agency plan long term, keep abreast of current developments in the fishery and develop teleological projects. (ii) Fishers with a dominating evaluative (present-oriented) agency constantly evaluate as well as re-evaluation their situations. Evaluative social practices are not teleological and are rather characterized in the fishery by decisions that are directed to present situations. This can also show in deviant behaviour (iii) Fishers with a dominating iterational (past-oriented) agency are characterised through the iteration of known schemes of action, which therefore reproduce social practices constantly. Such iterational aspects can be seen in fishers who solely apply gillnets. Furthermore, the analysis of bycatch practice resulted in two different types: (i) non-normalization of bycatch, mostly concerning the bycatch of harbour porpoise, a critical situation interrupting the daily routine and (ii) normalization of bycatch, mostly concerning the bycatch of seabirds which was understood as part of a routine. In applying the knowledge of different fisher types and bycatch practices to possible management instruments, numerous measures that can be considered by fisheries managers ii Abstract were identified and their potential effectiveness concerning fishers' heterogeneity was discussed.It is concluded that considering the social practices of resource users may be an important contribution to design effective natural resource management instruments. The inclusion of sociology, as well as sociologically established theories and qualitative reconstructive methods, has led to practice-relevant insights how knowledge on human behaviour may inform management and mitigate bycatch. – – Der Mensch nutzt seit jeher die natürlichen Ressourcen des Meeres, mit verschiedensten Auswirkungen die Fischbestände und die Meeresumwelt. Ein Problem, das sich aus der Interaktion der Menschen, insbesondere der Fischer, mit dem Meer ergibt, ist das Verfangen von Meeresvögeln und -säugetieren in Fischfanggeräten, insbesondere in Stellnetzen, wodurch diese luftatmenden Tiere ertrinken. Diese Vorfälle werden als Beifang bezeichnet. Stellnetze haben allerdings eine lange Tradition in der Fischerei in der Ostsee und sind weltweit eines der am häufigsten verwendeten Fanggeräte. Der Beifang von Seevögeln und Meeressäugern in der Stellnetzfischerei stellt daher eine Gefahr für den weltweiten Naturschutz dar. Die bisherigen Maßnahmen zur Verringerung des Beifangs im Fischereimanagement beruhen meist auf technischen und ökologischen Erkenntnissen. Trotz der Bedeutung für ein effektives Fischereimanagement mangelt es daher oft an Wissen über die Heterogenität der Handlungspraxis und Motivationen von Fischern. In dieser Dissertation wurde die deutschen Stellnetzflotte in der Ostsee betrachtet, um ein ontologisches Verständnis der sozialen Praktiken der Fischer zu entwickeln, das als Grundlage für das Management und die Entwicklung von Maßnahmen zur Beifangreduzierung und -vermeidung dient. [...]
urn:nbn:de:gbv:253-202205-dn064849-0
Keywords: 630; Fishers' agency; Bycatch discourse; Bycatch mitigation; Fisheries management; Social-science fisheries research; Handlungsfähigkeit von Fischern; Beifangdiskurs; Beifangreduzierung; Fischereimanagement; sozialwissenschaftliche Fischereiforschung